Investigate the scattering of electromagnetic waves from lanthanide nanoparticles by changing the size and shape of nanoparticles - Osamah Saud Salman; Tamer Khalil M Ali (Tikrit Journal of Pure Science, 2021)
The aim of this study was to evaluate the effect of change in particle size and shape of nano lanthanides and its effect on the distribution of electromagnetic waves. In this study, we investigated lanthanide nanoparticles for the scattering of electromagnetic waves in excitation factors such as the electronic properties of nanoparticles, the size and shape of nanoparticles, the temperature properties around nanoparticles and dielectric nanoparticles. In this study, lanthanide nanoparticles with CST software were used to simulate the scattering of electromagnetic waves. In this project, using the classical electromagnetic theory, the scattering of small dielectric particles in relation to this cross section of electromagnetic waves was investigated and the changes for different parameters were evaluated. Also, the rotation measured the cross-section of small particles by changing the parameters. Lanthanide nanoparticles in the 60 GHz to 120 GHz band were used to study the scattering of electromagnetic waves. The results showed that the yield of lanthanide particle nanometers was more than five nanometers in diameter and more than ten nanometers. We have shown that with the angular scattering of electromagnetic waves, lanthanide nanoparticles are more oval and more than a spherical shape.